Diversity, Ecological Role and Biotechnological Potential of Antarctic Marine Fungi - Stefano Varrella; Giulio Barone; Michael Tangherlini; Eugenio Rastelli; Antonio Dell’Anno; Cinzia Corinaldesi (Journal of Fungi, 2021)
The Antarctic Ocean is one of the most remote and inaccessible environments on our planet and hosts potentially high biodiversity, being largely unexplored and undescribed. Fungi have key functions and unique physiological and morphological adaptations even in extreme conditions, from shallow habitats to deep-sea sediments. Here, we summarized information on diversity, the ecological role, and biotechnological potential of marine fungi in the coldest biome on Earth. This review also discloses the importance of boosting research on Antarctic fungi as hidden treasures of biodiversity and bioactive molecules to better understand their role in marine ecosystem functioning and their applications in different biotechnological fields.